Panel Cointegration Analysis with Xtpedroni. (September 2014) - Neal, Timothy
In this article, I introduce the new commandxtpedroni, which implements the Pedroni (1999, Oxford Bulletin of Economics and Statistics 61: 653–670; 2004, Econometric Theory 20: 597–625) panel cointegration test and the Pedroni (2001, Review of Economics and Statistics 83: 727–731) group-mean panel-dynamic ordinary least-squares estimator. For nonstationary heterogeneous panels that are long (large T ) and wide (large N ), xtpedroni tests for cointegration among one or more regressors by using seven test statistics under the null of no cointegration, and it also estimates the cointegrating equation for each individual as well as the group mean of the panel. The test can include common time dummies and unbalanced panels.